A history of symposium on stochastic systems theory and its applications, Japan 1968–2018. (March 2020) - Katayama, Tohru
Abstract: This article is an extended version of my lecture on a history of the Symposium on Stochastic Systems Theory and Its Applications (SSS) delivered at the 50th Anniversary meeting on November 1, 2018 (Katayama, 2018 ). It is shown why and how the Symposium was launched in Kyoto 1968; this is a part of early history of automatic control in Japan. Also, activities of SSS for the past 50 years are briefly reviewed chronologically from my personal point of view.